Implementation of Indonesian Cultural Learning: Indonesian Language and Mathematics Literacy Education for Children of Indonesian Migrant Workers in Kuala Lumpur - Dewi Lely Ambarwati; Desi Destiana Agusman; Siti Nur Azizah (Journal of Society, Community and Business Development, 2025)
Some factors cause PMI (Indonesian Migrant Workers) children not to be able to attend formal schools, one of which is because the documents are not fulfilled, and the lack of information about Indonesia is also a problem faced by Indonesian migrant children. Therefore, here, Semangat Muda Indonesia and Youth ID provides space for the Indonesian community to contribute positively to teaching and help children there in academic and non-academic teaching programs for Indonesian migrant children in Kuala Lumpur so that they understand and understand information about Indonesian culture and also their academic learning. The learning provided is about learning Indonesian culture, Indonesian language literacy education, and mathematics. The purpose of this teaching activity is to provide an understanding of the culture and customs of Indonesia, which are very diverse, so that Indonesian children living in Kuala Lumpur can be close to their culture and foster a sense of love for their homeland, namely Indonesia, then with the teaching of Indonesian Language it is hoped that it can increase children's literacy preferences for reading books and learning mathematics, namely to increase insight and knowledge to children.